Nanofluid Applications in Future Automobiles: Comprehensive Review of Existing Data - Senthilraja, S.; Karthikeyan, M.; Gangadevi, R. (Nano-Micro Letters, 2011)
In recent years fluids containing suspension of nanometer sized particles have been an active area of research due to their enhanced thermo physical properties over the base fluids like water, oil etc. Nanofluids possess immense potential applications to improve heat transfer and energy efficient in several areas including automobile, micro electronics, nuclear, space and power generation. Nowadays most of the researchers are trying to use the nanofluids in automobile for various applications such as coolant, fuel additives, lubricant, shock absorber and refrigerant. The goal of this paper is to create the awareness on the promise of nanofluids and the impact it will have on the future automotive industry. This paper also presents a comprehensive data of nanofluids application in automobile for various aspects.